1998
DOI: 10.1046/j.1469-8137.1998.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Tansley Review No. 95: 15N natural abundance in soil–plant systems

Abstract: The following citations were erroneously omitted from the ‘References’: Groffman PM, Zak DR, Christensen S, Mosier A, Tiedje JM. 1993. Early spring nitrogen dynamics in a temperate forest landscape. Ecology74: 1579–1585. Handley LL, Brendel O, Scrimgeour CM, Schmidt S, Raven JA, Turnbull MH, Stewart GR. 1996. The 15N natural abundance patterns of field‐collected fungi from three kinds of ecosystems. Rapid Communications in Mass Spectrometry10: 974–978. Handley LL, Daft MJ, Wilson J, Scrimgeour CM, Ingleby K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
405
5
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(432 citation statements)
references
References 0 publications
10
405
5
12
Order By: Relevance
“…, Padgett et al. ), and cities with older neighborhoods in the urban areas may experience greater soil N losses over time than the younger homes in suburban and exurban areas, enriching the remaining soil N and contributing to the differences in soil δ 15 N (Högberg ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Padgett et al. ), and cities with older neighborhoods in the urban areas may experience greater soil N losses over time than the younger homes in suburban and exurban areas, enriching the remaining soil N and contributing to the differences in soil δ 15 N (Högberg ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil δ 15 N enrichment results from a proportional increase in enriched N sources (Kendall et al. ), or from soil N cycling processes that increase soil 14 N losses (Högberg , Robinson ). Older homes in BAL, BOS, and PHX are in urban rather than suburban/exurban residential areas suggesting that enriched urban δ 15 N sources may contribute to greater soil δ 15 N in yards around older homes (Ammann et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al (2002) also concluded that 15 N is a poor tracer of the N sources applied. Although δ 15 N for plant matter primarily reflects the isotope signature of the N source, discrimination may occur during N uptake, assimilation and redistribution within the plant (Högberg, 1997; Robinson et al , 1998). There is also evidence of genotypic variability in isotopic fractionation (Robinson et al , 2000; Ellis et al , 2002; Coque et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A non‐carnivorous plant can be used as a suitable reference for the soil N contribution. However it is known that microhabitat, rooting depth and mycorrhizal system (Gebauer & Schultze 1991; Hogberg 1997; Schmidt & Stewart 1997; Hobbie et al. 2000) can have strong effects on the δ 15 N value of a plant.…”
Section: Methodsmentioning
confidence: 99%